2011
DOI: 10.1259/dmfr/30045588
|View full text |Cite
|
Sign up to set email alerts
|

Detecting young Japanese adults with undetected low skeletal bone density using panoramic radiographs

Abstract: Objective: The cortical width below the mental foramen of the mandible determined from panoramic radiographs is a useful screening tool for identifying elderly individuals with a low skeletal bone mineral density (BMD). However, whether the mandible cortical width (MCW) is useful for identifying a low skeletal BMD in men and women of 40 years or younger is not known. Methods: The BMD of the calcaneus was measured by ultrasonography bone densitometry in 158 men and 76 women aged 18-36 years. A logistic regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 19 publications
(20 reference statements)
5
24
1
3
Order By: Relevance
“…Mandibular cortical width and porosity seen on dental panoramic radiographs have been shown to be parameters which are potentially useful for assessing an individual's risk of systemic osteoporosis [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Mandibular cortical width and porosity seen on dental panoramic radiographs have been shown to be parameters which are potentially useful for assessing an individual's risk of systemic osteoporosis [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…No suitable machines are available in Laos. A number of studies have indicated that a dental panoramic radiograph may be a suitable tool to measure bone mineral densities [12][13][14][15][16][17][18][19][20]24,25) . In this study digital panoramic radiographic equipment was used to obtain the images.…”
Section: Discussionmentioning
confidence: 99%
“…In this study digital panoramic radiographic equipment was used to obtain the images. Digital panoramic technologies have the benefi t of eliminating errors associated with processing and providing the opportunity of using digital enhancement and measuring tools 7,15,16,21,23) . Digital panoramic radiography also limits radiation exposure as it requires a lower dose than conventional panoramic radiography for image formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nos pacientes com osteoporose, a cortical óssea aparece mais fina e com maior grau de erosão, quando comparado a pacientes com DMO normal. O índice mais utilizado nos estudos é o índice quantitativo mentual, que avalia a espessura da cortical mandibular abaixo do forame mentual (Alonso et al, 2011;Taguchi et al, 2011).…”
Section: Introductionunclassified